PENGARUH PENYIMPANAN TERHADAP VIABILITAS BENIH KEDELAI - Nana Danapriatna (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2007)
Seed qualify is one that determines the productivity of soybean. Quality seeds obtained through a series of seed technology activities starting from seed production, seed processing, seed testing, certification of seeds to seed storage. Storage of seeds is one of the soy harvest handling of the whole technology is important to maintain seed quality. The main objective of seed storage is to maintain the viability of the seeds along as possible and to maintain the fsiologis quality of seeds during the period storage by inhibiting the deterioration speed of the seed. Factors that influence the viability of seeds during storage is divided into internal and external factors. Internal factors include genetic trait, the power to grow and Vigor, skin conditions and initial seed moisture content. External factors such as packaging of seeds, gas composition, temperature and humidity save space.